Is the use of negative pressure wound therapy for a malignant wound legitimate in a palliative context? "The concept of NPWT ad vitam": A case series. (May 2015) - Riot, Samuel; de Bonnecaze, Guillaume; Garrido, Ignacio; Ferron, Gwenaël; Grolleau, Jean-Louis; Chaput, Benoit
Background: The management of malignant wounds remains particularly difficult. They are often malodorous, highly exuding, and painful. In this context, the use of negative pressure wound therapy is usually not recommended. It is, however, an effective procedure for maintaining a good quality of life in certain palliative situations. Case presentation: Five patients underwent negative pressure wound therapy for a malignant wound in our unit. Three had sarcomas, one patient had a parietal recurrence of breast carcinoma, and one patient had melanoma. They were in a metastatic palliative situation and were no longer receiving specific treatment. Case management and outcomes: The patients reported a decrease in odor and exudates with negative pressure wound therapy, compared with conventional dressings. No patients complained of pain associated with the suction system itself. Fewer dressing changes reduced the pain and encouraged the resumption of social interactions. The average duration of negative pressure wound therapy before the death of the patients was 49 days. No complications or bleeding were observed. The duration of the patients' stay was shortened by implementing negative pressure wound therapy at home. Conclusion: We report on our experiences with five patients for whom manufacturers and health authorities contraindicated the use of negative pressure wound therapy because of its potential to encourage tumor growth, although it was considered to be beneficial for all of these patients. This procedure may offer an alternative to conventional wound dressings at the end of life and improve the quality of life of patients by controlling the three most disabling elements: the odor, exudate, and pain associated with changing the dressings. Miniaturization and lower costs could promote the systematic use of negative pressure wound therapy.